Excess light aggravates the harmful effects of drought and chilling stresses in green leaves of natural rubber (Hevea brasiliensis) - Jacob J; Alam B; Annamalainathan K; Nair D B; Sreelatha S (2nd International Congress of plant physiology on sustainable plant productivity under changing environment 8-12 January, 2003, New Delhi)
Hevea brasiliensis is the only commercial source of natural rubber, a vital industrial raw material of strategic importance. Being a native of wet and warm forest of the Amazon valley, this perennial tree species is leaa adapted to dry, semi arid and cold conditions. Drought and temperature extremes are two important abiotic stress that limit the growth and productivity of this crop. In this C3 species, leaf photosynthesis saturates at about 800 to 1000 mmol m-2s-1 under non-stress conditions. However the light saturation point sharply declines when plants are experiencing an abiotic stress. Under such conditions the amount of light that is over and above the light saturating point becomes excess and this aggravates the detrimental effects of abiotic stresses. Excess light leads excess excitation energy in the photosynthesis apparatus causing an imbalance between the photochemical reactions and carbon metabolism as studied from simultaneous measurements of gas exchange and chlorophyll fluorescence. The overexcitation of the system results in the production of various active oxygen species and free radicals resulting in severe oxidative damage. A few drought tolerant clones with better capacity to quench excess excitation energy and improved anti-oxidant mechanisms have been identified. Some of these drought tolerant clones also maintained better water use efficiency as evident from the stable isotope (carbon and oxygen) compositions of their tissues. The crop improvement strategies for this tree species to cope with abiotic stresses are discussed.
Keywords: Chilling; Drought; Hevea brasiliensis; Stress